Further Enhancing Piezoelectric Properties by Adding MnO2 in AgSbO3‐Modified (Li, K, Na)(Nb, Ta)O3 Lead‐Free Piezoceramics. Issue 11 (30th July 2016) - Liu, Qing; Zhu, Fang‐Yuan; Zhao, Lei; Wang, Ke; Li, Longtu; Li, Jing‐Feng
Abstract : This work investigated the effect of MnO2 addition on the phase structure, microstructure, and electrical properties of AgSbO3 ‐modified (Li, K, Na)(Nb, Ta)O3 (abbreviated as LKNNT‐AS) lead‐free piezoelectric ceramics with an optimized composition endowed with a state of two‐phase coexistence. A small amount (0.1 wt%) of MnO2 can significantly further enhance the piezoelectric property of LKNNT‐AS ceramics, whose piezoelectric constant d 33 and converse piezoelectric coefficient d 33 * as well as planar electromechanical coupling factor k p reach 363 pC/N, 543 pm/V, and 0.49, respectively. The temperature stability of piezoelectricity in MnO2 ‐modified LKNNT‐AS samples also improved, which is associated with the more uniform and better thermally stable ferroelectric domains that were revealed by piezoresponse force microscopy.